Report cards: Parental preferences, information and school choice in Haiti - Michael Borger; Gregory Elacqua; Isabel Jacas; Christopher Neilson; Anne Sofie Westh Olsen (Yale University, Economic Growth Center, 2024)
This paper studies school choice and information frictions in Haiti. Through a randomized control trial, we assess the impact of disclosing school-level test score information on learning outcomes, prices, and market shares. We find evidence that in markets where information was disclosed, students attending private schools increased test scores. The results also suggest private schools with higher baseline test scores increased their market share as well as their fees when the disclosure policy is implemented. While prices and test scores were not significantly correlated in the baseline survey, they exhibited a significant and positive correlation in treatment markets after information disclosure. These results underscore the potential of information provision to enhance market efficiency and improve children's welfare in context such as Haiti.
Keywords: 330; private schooling; information asymmetries; school choice; economic development; Haiti